Skipping Breakfast and Its Associated Factors Among Undergraduate Students: Skipping Breakfast and its Associated Factors - Rai, Fuad Hameed; Niazi, Ayesha; Maqsud, Mahliqa; Fatima Rai, Aliezeh; Niazi, Areej (Pakistan Journal of Health Sciences, 2023)
Breakfast, which literally means breaking the overnight fast, is the day's first meal. Objective: To determine the factors associated with skipping breakfast among undergraduate students of Akhtar Saeed Medical and Dental College located at Canal Campus Lahore, Pakistan. Methods: A cross-sectional survey was conducted using a self-designed health assessment questionnaire in which demographic profile, anthropometric measurements, open-ended and close-ended questions were included which noted the major physiological and psychological aspects of skipping breakfast. The study was conducted on the total sample of 180 students both adult males and females of age ≥18years of age which were selected in the Akhter Saeed Medical and Dental College, Canal Campus Lahore, Pakistan. Results: Out of total sample 180, only 62 participants (34%) were consuming breakfast and 118 participants (66%) were not having breakfast in morning. The highest recorded reason for skipping of breakfast was 29 participants (16%) do not like to eat in morning also do not have enough time to consume breakfast in morning and 62 participants (34%) had no reason for not consuming breakfast. Skipping of breakfast was also associated with (91%) feeling hungry, not having energy, feeling headaches, grumpy, lethargic, trouble paying attention in class and tired whereas 17 participants (9%) had stomachache and dizziness. Conclusions: Participants agreed that breakfast is the important meal of every morning. They found consumption of breakfast consisting of more fruits and vegetables, dairy products and fibers are proved to make an individual healthy as it provides enough energy to stay focused and active throughout the day.